Quels effets du numérique et du multimédia sur les processus attentionnels des apprenants de langues ? - Stéphanie Roussel (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In second language learning situations, do digital technologies allow for concentration or do they, on the contrary, lead to a split of a learner's attention to language? Do digital technologies support second language processing? Under which conditions and for which learners could this apply? Attention, as it is currently conceived by cognitive psychology, involves the selection of information, the processing and manipulation of this information in memory, and the awareness and control of one's actions. These different aspects of attention allow to examine, by reporting on several experiments, how digital technologies change the allocation of attentional resources, when it comes to learning a second language.